(untitled) (Research, Society and Development, 2023)
Rio Grande do Sul does not have a Technical Regulation of Identity and Quality (RTIQ) for honey from Stingless Bees (ASF), consequently the commercialization of this food happens informally and without hygienic-sanitary inspection to guarantee its food safety. Therefore, the present study aimed to generate subsidies for the elaboration of an RTIQ for the ASF Gaucho honey. For this purpose, the physical-chemical characterization of 24 samples of ASF honey, donated by 9 members of the Association of Meliponicultores do Vale do Alto Taquari, was carried out. The collections were carried out between February 25th and March 5th, 2018, according to the availability of excess honey in each meliponary. Physical-chemical analyzes were carried out for the following parameters: Acidity, Reducing Sugars, Hydroxymethylfurfural (HMF), Mineral Residues, Diastasis, Insoluble Solids and Humidity, in addition to the botanical predominance identification. The results of this study were compared with the RTIQ’s of ASF honey from the states of BA, AM, PR and SP and with national legislation. We can conclude that in relation to the parameters of Reducing Sugars, Moisture, Insoluble Solids, Ashes and Acidity, they all comply with the mentioned regulations. While for the parameters Diastasis and HMF the framing was partial. Therefore, it is possible keeping the particularities of each region and the diversity of ASF species, to use the existing RTIQ’s as a parameter for the elaboration of a document for RS.